Understanding Compliant Behavior During a Pandemic: Contribution From the Perspective of Schema-Based Psychotherapy - Offurum, Chino José; Leibetseder, Max; Jenull, Brigitte (Frontiers in Psychology, 2022)
Objective: The current study examined whether compliance with anti-pandemic measures during the COVID-19 pandemic relates to (a) importance of the fulfillment of core psychological needs, namely relationship, self-esteem, efficacy and pleasure; to (b) coping behavior styles, namely surrender, self-soothing, divert-attention and confrontation; and to (c) worries or concerns beyond Covid-19 which may impair well-being. Methods: This study used a cross-sectional design and online survey data from responses to a structured questionnaire developed within the theoretical framework of schema-based psychotherapy on psychological needs and coping behavior styles from 740 participants in Central Europe and West Africa. Results: Analysis indicated that people with the psychological needs of “pleasure” and “efficacy” and the coping style of “surrender” were more likely to comply with anti-pandemic measures. We also found that people with the coping style of “confrontation” were less likely to comply. There were no statistically significant relationships between compliance and “relationship,” “self-esteem,” “self-soothing,” “divert attention,” and “existential concerns.” Discussion: Our findings indicate that how likely a given individual is to comply with prescribed pandemic countermeasures varies based on their specific psychological needs and behavior styles. Therefore, to control contagion during a pandemic, authorities must recognize the relevance of human need fulfillment and their behavior styles and accordingly highlight and encourage admissible and feasible actions. The findings demonstrate that some individual differences in core psychological needs and coping behavior patterns predict compliance behavior.